Analyzing the Influence of Occupational Licensing Duration and Grandfathering on Wage Determination. Issue 2 (23rd April 2021) - Han, Suyoun; Kleiner, Morris M.
Abstract : The length of time from the implementation of an occupational licensing statute (i.e., licensing duration) may matter in influencing labor‐market outcomes as entry requirements evolve. In addition, states enact grandfather clauses that allow existing workers to continue employment following these regulations, while ratcheting up requirements to increase entry costs for new entrants. We analyze the labor‐market influence of the duration of occupational licensing statutes for fifteen state universally licensed occupations over a 75‐year period. We find a positive nonlinear wage effect for licensing duration. Further, we find that occupational licensing raises the wages of grandfathered workers by almost 5 percent. The licensed occupations, however, exhibit heterogeneity in outcomes. Duration of occupational licensing influences wage determination when measured over longer time periods.